INCREASING CUSTOMER LOYALTY THROUGH PERCEIVED SERVICE QUALITY AND RELATIONSHIP MARKETING IN CLEANING SERVICE COMPANY - Yohanes A. Panuntas; Ujang Sumarwan; Prita Prasetya (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Background:KThe environmental conditions of the cleaning services industry are very competitive and market growth tends to be slow. Objective: This study aims to analyze the variables that drive the creation ofcustomer loyaltyin B2B cleaning service companies such as perceived service quality variables through the INDSERV (Industry Service) measurement instrument which consists of potential quality, hard process quality, soft process quality, and output quality, then relationship quality through its main components, namely customer satisfaction, trust, and commitment. Design/methodology/approach: This study used 196 customer respondents who were still working together and not working together. The data collection technique uses an online survey questionnaire via Google Form.This study uses a quantitative approach and analysis using descriptive analysis and PLS-SEM. Findings/Results:Findingsshows that output quality and commitment have a direct positive influence on customer loyalty.ThenPotential quality and soft process quality have a positive influence on customer loyalty indirectly through commitment. Conclusion:The results of this study emphasize the importance ofpotential quality, soft process quality,output quality, andcommitment to increasing customer loyalty. Originality/value (Current state):This study contributes to the existing literature by providing empirical insights into the role of output quality andCommitment directly increases customer loyalty, as well as potential quality and soft process quality, which indirectly increase customer loyalty through commitment in the B2B cleaning services sector. These findings offer practical recommendations for strategies to increase customer loyalty for B2B cleaning service companies.